Subjective measures of well-being for developing countries - Camfield, L (Kluwer Academic Publishers, 2004)
The paper explores the conceptual and methodological issues entailed in using subjective measures of well-being in developing countries. In the first part I define, situate and contrast subjective quality of life (QoL), subjective well-being (SWB), and well-being. I also look at the conceptual and methodological shortcomings of subjective measures of well-being and suggest ways of overcoming these by combining different approaches. I then explore how an expanded concept of subjective quality of life fits into the theoretical framework of the UK-based Well-being in Developing Countries study (or WeD), specifically how it plans to produce a new, “development-related” profile of quality of life, drawing on the methodology of the WHOQOL group (1995; 1998).